THE DIALECTICS OF SUFI COUNSELING AND MAINSTREAM COUNSELING IN BULLYING CASES - Erliani, Susi (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2024)
This study concludes that Sufi counseling and mainstream counseling, while distinct in their approaches, can be effectively integrated to address psychological issues such as bullying. Sufi counseling prioritizes the spiritual dimension, fostering inner peace, empathy, and a profound understanding of one’s role within the broader societal context. In contrast, mainstream counseling is grounded in psychological theory and practice, focusing on the behavioral and cognitive aspects of individuals, thereby providing evidence-based interventions and practical strategies for managing bullying behaviors.The findings of this study suggest that a complementary application of both counseling approaches within the school environment is highly beneficial for addressing bullying. Sufi counseling can enhance students’ emotional and spiritual well-being, while mainstream counseling offers a more pragmatic approach to modifying behaviors and implementing concrete solutions.Additionally, it is recommended that schools invest in specialized training for counselors and educators in Sufi counseling techniques. Creating space for approaches rooted in religious and spiritual values as part of character development programs would not only aid in addressing bullying but also reinforce the moral and ethical foundation essential for students’ social interactions. Key Words: Sufistic counseling; mainstream counseling; bullying; difference; equality